Deficit Financing, Controls and Movement of Prices in India since 1947 - Vasudevan, A. (Bombay : New York : Allied Publishers, 1967)
This study is largely based on a thesis approved for the award of Doctor of Philosophy of Banaras Hindu University in 1964.The two parts in it deal with the theoretical and applied aspects of the problem.
osc 20/06/17
Loans
Keywords: Deficit financing; Deficit financing